Visionen von Natur vor uns. Alfred Ehrhardt fotografiert und filmt Urformen der Natur (Studia theodisca, 2015)
What did nature look like before it was destroyed by modern civilization? That is a question that was at the center of modernist art photography. It also resonates today in the context of environmental debates. On the example of the art work of Bauhaus photographer and cinematographer Alfred Ehrhardt, the artistic project of portraying nature “before us” is analyzed as an aesthetic project that positions itself before and next to the Anthropocene, i.e., the geological concept that foregrounds a radical interconnectivity between humans and nonhuman nature in our post-industrial era of mankind.